Prevalence of invehicle smoking and secondhand smoke exposure in Uruguay. Issue 6 (19th January 2018) - Llambi, Laura; Barros, Mary; Parodi, Carolina; Pippo, Antonella; Nunez, Virginia; Colomar, Mercedes; Ciganda, Alvaro; Cavalleri, Fiorella; Goyeneche, Juan J; Aleman, Alicia
Abstract : Introduction: Protection from secondhand smoke (SHS) is one of the fundamental principles of the WHO Framework Convention for Tobacco Control. Objective data on SHS exposure in vehicles in South America is scarce. This study aimed to estimate prevalence of smoking inside vehicles. Methods: The point prevalence of smoking in vehicles was observed, and a method for estimating smoking prevalence was piloted. Results: We observed 10 011 vehicles. In 219 (2.2%; 95% CI 1.91 to 2.49) of them, smoking was observed, and in 29.2% of these, another person was exposed to SHS. According to the 'expansion factor' we constructed, direct observation detected one of six to one to nine vehicles in which smoking occurred. The observed prevalence of smoking in vehicles (2.2%) could reflect a real prevalence between 12% and 19%. In 29.2% (95% CI 23.6 to 35.5) and 4.6% (95% CI 2.2 to 8.3) of vehicles in which smoking was observed, another adult or a child, respectively, was exposed to SHS. Conclusions: Smoking was estimated to occur in 12%–19% of vehicles, with involuntary exposure in one of three of vehicles observed. These data underscore a need for new public policies to eliminate SHS in vehicles to protect public health.